Mirbobo Naqshbandi’s Comments about Human Perfection, Polishing the Soul, Giving it Spiritual Nourishment - Alisher Rajabov (International Journal on Integrated Education, 2023)
The article analyzes the opinions expressed in the preface of the work “Mir’otus solikyyn” written for followers of the order by Sufi Mirbobo Naqshbandi, who contributed to the development of the Naqshbandi order in India. At the same time, the author’s thoughts related to the Naqshbandi order were translated from Persian and researched.